Perencanaan Pembangunan Berbasis Partisipatifdi Kelurahan Mario Pulana Kecamatan Camba Kabupaten Maros - Ridwan, Yuniarti M; Fatmawati, Fatmawati; Rahim, Samsir (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2022)
The purpose of this study was to determine the implementation of participatory-based development planning in Mario Pulana Village, Camba District, Maros Regency.The type of research used is a qualitative research method with a descriptive type of research. Data collection techniques using observation, interviews and documentation.The results of this study show 3 (three) processes of implementing participatory-based development planning in Mario Pulana Village, Camba District, Maros Regency, namely: 1) Focusing on the Interest of the Community, namelythat the fulfillment of all proposals given by the community through Musrenbang activities and Coordination Meetings, but coordination meetings are often not carried out by the Head of the Environment, 2) Participatory, that the involvement of the community in Mario Pulana Village, Camba District, Maros Regency has been active in providing suggestions, opinions, ideas and even providing energy/materials, but the presence of the community is still very little, and 3) Synergy, namely an agreement between the government and the community in accommodating aspirations given by the community by making two agreements, but there are still many proposals that cannot be fulfilled at the sub-district level. Keywords: Development Planning, Participatory